Analisis Systematic Literatur Review : Corporate University Sebagai Strategi dalam Meningkatkan Kompetensi Pegawai - Setiawati, Rini; Sutisna, Anan; Saefudin, Yetty Supriyati (Jurnal Pendidikan Ekonomi Undiksha, 2023)
The results of this study will provide an understanding of Corporate University how it affects competence, the implementation process is and how knowledge management (KM) is in the implementation of CorpU. The research method used is SLR by identifying, analyzing, based on the results of previous research obtained through google schoolar and scopus. The search process is used to obtain relevant sources to get answer research questions (RQ). The data is in the form of secondary data, The keywords in the literature search are "Corporate University, and Knowledge Management". The results showed that there was an effect of CorpU implementation on employee competence. In building CorpU, there are several stages that can be carried out starting from the preparation stage (organizational diagnosis), providing facilities and infrastructure, building collaboration to implementing CorpU. One of the important pillars in CorpU is (KM) where the important benefit of KM is that it allows knowledge assets to be stored properly and can be reused when needed. CorpU is the right solution in reducing the competency gap. From many studies, CorpU implementation is able to improve organizational performance because learning in the organization is integrated.